PERANAN AUTOMATIC VOLTAGE REGULATOR SEBAGAI PENGENDALI TEGANGAN GENERATOR SINKRON - Nurdin, Alimin; Azis, Abdul; Rozal, Reri Aresta (Universitas PGRI Palembang, 2018)
Synchronous generators are electrical machines that function to convert mechanical energy into electrical energy. Synchronous generators have problems that are voltage instability when the load changes, so it requires equipment that can control the stability of the synchronous generator voltage, namely Automatic Voltage Regulator (AVR). Automatic Voltage Regulator (AVR) is a voltage regulating device used in synchronous generators to stabilize the output voltage generated from a synchronous generator. Automatic Voltage Regulator (AVR) works by regulating the excitacy of the exciter, if the load increases then the Automatic Voltage Regulator (AVR) will command the exciter to work by increasing the reverse excitation current if the load decreases then the Automatic Voltage Regulator (AVR) will command the exciter to reduce excitation flow. ABSTRAK Generator sinkron merupakan mesin-mesin listrik yang berfungsi untuk mengkonversi energi mekanik menjadi energi listrik. Generator sinkron mempunyai permasalahan yaitu ketidakstabilan tegangan pada saat perubahan beban, sehingga dibuthkan peralatan yang dapat mengendalikan kestabilan tegangan generator sinkron yaitu Automatic Voltage Regulator(AVR).Automatic Voltage Regulator (AVR) merupakan sebuah divais pengatur tegangan yang digunakan pada generator sinkron untuk menyetabilkan tegangan keluaran yang dihasilkan dari generator sinkron. Automatic Voltage Regulator (AVR) bekerja dengan mengatur arus penguatan (excitacy) pada eksiter, apabila beban bertambah maka Automatic Voltage Regulator (AVR) akan memerintahkan eksiter untuk berkerja dengan menambah arus eksitasi sebaliknya apabila beban berkurang maka Automatic Voltage Regulator (AVR) akan memerintahkan eksiter untuk mengurangi arus eksitasi